2021
DOI: 10.1002/ceat.202000463
|View full text |Cite
|
Sign up to set email alerts
|

Study of CO2 Sorption Kinetics on Electrospun Polyacrylonitrile‐Based Carbon Nanofibers

Abstract: Electrospun carbon nanofibers (CNFs) exhibit a decent CO2 sorption capacity and outstanding CO2/N2 selectivity. In this work, the sorption rate as another practically relevant parameter for CO2 adsorption is analyzed for different carbonization temperatures. Equilibration curves obtained from different CO2 sorption isotherms are discussed qualitatively and quantitatively, employing empirical models for pseudo‐first‐ and second‐order reactions. The sorption rate constants are found to be highly dependent on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…(e) Corresponding desorption curves. (f) Mass transfer coefficients resulting from the modeled breakthrough curves ( k LDF ) shown in (a–d) in comparison to results from static gas adsorption experiments ( k PFO ) [24] . The breakthrough curves were measured on PAN‐based CNFs carbonized at various temperatures ranging from 600 to 900 °C with 3 % CO 2 in Helium at 5 bar, 0 °C, and a flow rate of 100 mL min −1 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…(e) Corresponding desorption curves. (f) Mass transfer coefficients resulting from the modeled breakthrough curves ( k LDF ) shown in (a–d) in comparison to results from static gas adsorption experiments ( k PFO ) [24] . The breakthrough curves were measured on PAN‐based CNFs carbonized at various temperatures ranging from 600 to 900 °C with 3 % CO 2 in Helium at 5 bar, 0 °C, and a flow rate of 100 mL min −1 .…”
Section: Resultsmentioning
confidence: 99%
“…It was found that the sample prepared at 900 °C exhibits a flowrate-depend- (a-d) in comparison to results from static gas adsorption experiments (k PFO ). [24] The breakthrough curves were measured on PAN-based CNFs carbonized at various temperatures ranging from 600 to 900 °C with 3 % CO 2 in Helium at 5 bar, 0 °C, and a flow rate of 100 mL min À 1 . The desorption curves were measured with 100 % He at 5 bar, 273 K, and 97 mL min À 1 .…”
Section: Chemsuschemmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional superior adsorption properties, [10,11] such as high CO 2 selectivities, enable the utilization of CNFs as carbon capture material. [12][13][14][15] Furthermore, the interplay of both, electrical and adsorption properties, is essential for electrical conductive adsorbents employed in the energy efficient electrical swing adsorption (ESA) process. [16][17][18] To tailor the overall macroscopic properties of the CNFs to the respective application, an exact understanding of the micro-and nanoscale electrical properties of individual fibers and of the fiber networks is crucial.…”
Section: Introductionmentioning
confidence: 99%
“…[46] This study reveals the effect of the carbonization temperature on nano-and microscale electrical properties of CNFs and their networks. Therefore, as in previous works, [7,[12][13][14][15]22,23] different electrospun PAN-based CNF mats carbonized at temperatures within the range of 600-1000 °C were prepared, and each sample has been investigated by PeakForce Tunneling Atomic Force Microscopy (PF TUNA, Bruker), a force-distance curve based C-AFM mode. First, at the microscale, the interconnections of multiple fibers were investigated for each sample.…”
Section: Introductionmentioning
confidence: 99%